Cunoniaceae endémicas del Perú - León, Blanca (2006)
This family is typical of the Very Humid montane forests. The Cunoniaceae are represented in Peru by 41 species in the genus Weinmannia (Brako & Zarucchi, 1993), all of them shrubs and trees. Here we recognize six species and two varieties as endemics. We applied IUCN categories and criteria to five species. Endemic Cunoniaceae are found in the Mesoandean and Very Humid Premontane Forests regions. Two endemic species have been found in Peru´s protected areas system.